Ethical leadership, organizational climate, team work effectiveness, and employe performance - Budi Prasetya, Dio Eko (INDONESIAN JOURNAL OF SUSTAINABILITY, 2023)
This study aims to analyze the influence of ethical leadership, organizational climate on employee performance with team work effectiveness as variable interverning. This study was carried out to the employees of PT. Misaja Mitra Pati. The population of this study was around 110 employees of PT. Misaja Mitra Pati. Based on purposive sampling there were 110 respondens. Data analysis of this study using SEM-PLS. The result of hypothesis test that shows the influence of ethical leadership on team work effectiveness and organizational climate on team work effectiveness is accepted. The result of hypothesis test that shows the influence of ethical leadership on employee performance and organizational climate on employee performance is accepted. The result of hypothesis test that shows the influence of team work effectiveness on employee performance is accepted.Â Keywords: Ethical leadership; Organizational climate; Team work effectiveness; Employee performance.